PERBEDAAN KOMBINASI MYOFASCIAL RELEASE TECHNIQUE DENGAN ULTRASOUND DAN KOMBINASI ISCHEMIC COMPRESSION TECHNIQUE DENGAN ULTRASOUND DALAM MENINGKATKAN KEKUATAN OTOT LEHER AKIBAT SINDROMA MIOFASIAL PADA PENJAHIT PAKAIAN DI KABUPATEN GIANYAR - Ni Made Intansari Tri Buana; Susy Purnawati; Sugijanto -; Komang Satriyasa; Nengah Sandi; M. Ali Imron (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Myofascial syndrome is a chronic condition arising from trigger point activation causing a decrease in neck muscle strength in tailor clothes. Purpose: To determine the different combinations of myofascial release technique with ultrasound and ischemic compression technique combination with ultrasound in increasing neck muscle strength due to myofascial syndrome on the tailor of clothes in saraswati convection guwang gianyar village. Method: This study used an experimental study with pre-test and post-test group design. The sample consisted of 22 people consisting of 11 people in each group. The first group was given myofascial release technique intervention with ultrasound and the second group was given ischemic compression technique with ultrasound. Intervention is given 3x a week for 2 weeks. Sampling technique with random sampling. The strength of neck muscle was measured by sphygmomanometer. Results: Paired Sample T-test test in Group 1 was obtained p= 0,000 (p <0,05) and in Group 2 the result was p = 0,002 (p <0,05) Meaningful differences before and after intervention in each group. The mean difference test of mean values with independent sample t-test after treatment between groups was 0.195mmHg (p> 0.05) which means that there is no difference between the two groups in increasing the strength of neck muscles. Conclusion: There is no difference between a combination of myofascial release technique with ultrasound and a combination of ischemic compression technique with ultrasound in increasing neck muscle strength due to myofascial syndrome in dressmaker. Suggestion: As reference in handling case of myofascial syndrome especially upper trapezius muscle